Different theoretical approaches at optical characterization of randomly rough silicon surfaces covered with native oxide layers. (21st May 2018) - Ohlídal, Ivan; Vohánka, Jiří; Mistrík, Jan; Čermák, Martin; Franta, Daniel
Abstract : Results of the optical characterization of randomly rough silicon surfaces covered with native oxide layers based on processing experimental data obtained by ellipsometry and reflectometry are presented. It is shown that the Rayleigh‐Rice theory is suitable theoretical approach for characterizing micro‐rough surfaces in contrast to effective medium approximation. Combination of the Rayleigh‐Rice theory and scalar diffraction theory is efficient and reliable approach for characterizing rougher surfaces with the rms values of heights larger than 10 nm. Thickness of native oxide layers and roughness parameters, ie, the rms values of heights and autocorrelation lengths, are determined for micro‐rough and rougher surfaces using the corresponding theoretical approaches.